A nonlinear quasi-zero-stiffness vibration isolation system with additional X-shaped structure: Theory and experiment. (1st September 2022) - Xiong, Yuanhao; Li, Fengming; Wang, Yu
Highlights: A nonlinear quasi-zero-stiffness vibration isolation system is proposed and designed. The vibration isolation system has ultra-low starting frequency for vibration isolation. The vibration isolation system has wide quasi-zero-stiffness range. Experiments are conducted to validate the theoretical and numerical results. Abstract: A novel nonlinear quasi-zero-stiffness (QZS) vibration isolation system with high load carrying capacity is proposed. By connecting X-shaped structure with a platform, the quasi-zero-stiffness vibration isolation system with additional X-shaped structure (X-QZS) is designed. The relationships of system restoring force and stiffness related to displacement are obtained by static modelling, and the influences of the parameters on the system stiffness are analyzed. In the dynamic analysis, the amplitude-frequency characteristics and transmissibility curves are calculated by the harmonic balance method. The correctness of the calculation results is verified by numerical simulation and vibration experiments. From the investigations, it is observed that the designed X-QZS system has a wide QZS interval, a small unstable interval, a low jump-down frequency, and a high load carrying capacity. These results can provide a useful reference for improving the performance of QZS vibration isolation systems.